2022
DOI: 10.3390/ijms232415800
|View full text |Cite
|
Sign up to set email alerts
|

The New General Biological Property of Stem-like Tumor Cells (Part II: Surface Molecules, Which Belongs to Distinctive Groups with Particular Functions, Form a Unique Pattern Characteristic of a Certain Type of Tumor Stem-like Cells)

Abstract: An ability of poorly differentiated cells of different genesis, including tumor stem-like cells (TSCs), to internalize extracellular double-stranded DNA (dsDNA) fragments was revealed in our studies. Using the models of Krebs-2 murine ascites carcinoma and EBV-induced human B-cell lymphoma culture, we demonstrated that dsDNA internalization into the cell consists of several mechanistically distinct phases. The primary contact with cell membrane factors is determined by electrostatic interactions. Firm contacts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 90 publications
0
8
0
Order By: Relevance
“…This study is the first step in creating a new technology for HSC genome reconstruction/equalization based on the discovered ability of poorly differentiated cells, including HSCs, to capture dsDNA by a natural mechanism described in previous studies ( 16 , 17 ). The proposed analysis is the basis for the technological platform for obtaining a primary in situ screenshot of the colony phenotype and genetic changes directly on plates.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This study is the first step in creating a new technology for HSC genome reconstruction/equalization based on the discovered ability of poorly differentiated cells, including HSCs, to capture dsDNA by a natural mechanism described in previous studies ( 16 , 17 ). The proposed analysis is the basis for the technological platform for obtaining a primary in situ screenshot of the colony phenotype and genetic changes directly on plates.…”
Section: Resultsmentioning
confidence: 99%
“…We discovered and described a new general biological property of stem cells of various genesis in our recent studies ( 15 - 17 ). It has been experimentally shown that HSCs, as well as all the analyzed low-differentiated cells of mammals, including tumor-initiating stem cells, are able to capture dsDNA from the environment by a natural mechanism.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This Special Issue entitled “Developmental Biology: Computational and Experimental Approaches” of the International Journal of Molecular Sciences includes six contributions as original articles [ 4 , 5 , 6 , 7 , 8 , 9 ], providing new information about the experimental and computational approaches that promote technical progress for research into developmental biology.…”
mentioning
confidence: 99%
“…A study by Petrova et al [ 8 ] provides a molecular-level summary of the results obtained from an eight-year-long research effort in the development of a therapeutic approach named ‘Karanahan’ to treat malignant neoplasms. The study started with an unexpected observation that Krebs-2 mouse ascites tumor cells are capable of internalizing extracellular double-stranded DNA (dsDNA) natively without any special transfection procedures [ 15 ].…”
mentioning
confidence: 99%